Dutton's orthopaedic examination, evaluation, and intervention - Dutton, Mark (New York : McGraw Hill, 2023)
"This book aims to provide the reader with a systematic and evidence-based approach to the examination and intervention of the orthopaedic patient as an expert on the movement system"--
Formerly CIP.
Includes bibliographical references and index.
Keywords: Orthopedics; Orthopedics -- Diagnosis; Orthopedic Procedures -- methods; Physical Therapy Modalities; Physical Examination -- methods; Musculoskeletal Diseases -- rehabilitation; Musculoskeletal Diseases -- diagnosis